Reputation in Bargaining and Durable Goods Monopoly - Ausubel, Lawrence M.; Deneckere, Raymond J. (Econometrica, 1989)
Your use of the JSTOR archive indicates your acceptance of JSTOR's Terms and Conditions of Use, available at